Community Behavior Patterns and the Relationship with the Profile of Vegetation Diversity of the Mangrove Ecosystem in Tamuku Village, North Luwu Regency - Muh. Yunus (Budapest International Research and Critics University, 2021)
The research aimed to describe community behavior patterns and their relation to the diversity profile of mangrove ecosystem vegetation in Tamuku Village, Tulang-tulang District, North Luwu Regency. This research used qualitative research by survey method. The data collection techniques used interview techniques and quadrant line-transect surveys and the data analysis technique used a line of thought that is divided into three stages, namely describing phenomena, classifying them, and seeing how the emerging concepts are related to one another. The results of this study were the profile of mangrove vegetation in Tamuku Village, which is still found in 30 varieties of true mangrove vegetation and eleven types of associated mangrove vegetation in the coastal area of Tamuku Village, Tulang-tulang District, North Luwu Regency, South Sulawesi. The condition of mangrove vegetation in Tamuku Village is currently very worrying due to human activities that cause damage such as the flow normalization project, opening of new ponds, garbage disposal, water pollution due to chemicals, and exploitation of mangrove forests for the necessities of life. As a result, there was damage to the ecosystem as well as a reduction in the area of vegetated land as a place for mangroves to grow and develop.